Users’ satisfaction with the public dental service: the discovery of new patterns - Fadel, Cristina Berger; Bordin, Danielle; Santos, Celso Bilynkievycz Dos; Carvalho, Deborah Ribeiro; Moimaz, Suzely Adas Saliba (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2019)
AbstractBackground Regarding to oral health, little has been advanced on how to improve quality within dental care.Objective The aim of this study was to identify the demographic factors affecting the satisfaction of users of the dental public service having the value of a strategic and high consistency methodology.Method The Data Mining was used to a secondary database, contemplating 91 features, segmental in 9 demographic factors, 17 facets, and 5 dominions. Descriptive statistics were extracted to a demographic data and the satisfaction of the users by facets and dominions, being discovered as from Decision Trees and Association Rules.Results the analysis of the results showed the relation between the demographic factor 'professional occupation' and satisfaction, in all of the dominions. The occupations of general assistant and home assistant with daily wage stood out in Association Rules to represent the lower level of satisfaction compared to the facets that were worse evaluated. Also, the factor ‘health unit's name’ showed relation with most of the investigated dominions. The difference between health units was even more evident through the Association Rule.Conclusion The Data Mining allowed to identify complementary relations to the user's perception about the public oral health services quality, constituting a safe tool to support the management of Brazilian public health and the basis of future plans.

ResumoIntrodução Em relação à saúde bucal, pouco se avançou sobre como melhorar a qualidade no atendimento odontológico.Objetivo O objetivo deste estudo foi identificar fatores demográficos que afetam a satisfação de usuários do serviço público odontológico, sob a análise de uma metodologia estratégica e de alta consistência.Método Aplicou-se a Mineração de Dados sobre um banco de informações secundárias, contemplando 91 características, as quais foram segmentadas em 9 fatores demográficos, 17 facetas e 5 domínios. Estatísticas descritivas foram extraídas dos dados demográficos e a satisfação dos usuários foi exposta por meio de facetas e domínios, sendo apresentados a partir de Árvores de Decisão e Regras de Associação.Resultados A análise dos resultados mostra relação entre o fator demográfico 'ocupação profissional' e a satisfação do usuário, em todos os domínios. As ocupações de assistente geral e empregado doméstico com salário diário destacaram-se nas Regras de Associação para representar o menor nível de satisfação em relação às facetas que foram mais mal avaliadas. De forma complementar, o fator 'nome da unidade de saúde' expôs relação com a maioria dos domínios investigados. A diferença entre as unidades de saúde mostrou-se ainda mais evidente por meio da Regra de Associação.Conclusão A Mineração de Dados permitiu identificar relações complementares à percepção do usuário sobre a qualidade dos serviços públicos de saúde bucal, constituindo-se em ferramenta segura para subsidiar a gestão da saúde pública brasileira e a base de planos futuros.
Satisfação de usuários com o serviço público odontológico: a descoberta de novos padrões
Keywords: evaluation of the health service; satisfaction; dental care; data mining; avaliação do serviço de saúde; satisfação; odontologia; mineração de dados